2023
DOI: 10.1038/s42003-023-04736-y
|View full text |Cite
|
Sign up to set email alerts
|

Future-proofing ecosystem restoration through enhancing adaptive capacity

Abstract: Social-ecological ecosystem restoration involves interacting challenges, including climate change, resource overexploitation and political instability. To prepare for these and other emerging threats, we synthesized key restoration and social-ecological systems literature and derived three guiding themes that can help to enhance the adaptive capacity of restoration sites: (i) work with the existing system, (ii) create self-sustaining, adaptive systems, and (iii) foster diversity and participation. We propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The last feature highlighted by participants was the importance of pursuing a long-term vision for restoration projects. Although this might seem obvious, the long-term viability of restoration interventions is often neglected in practice (Frietsch et al 2023). This is, among others, caused by limited funding (Höhl et al 2020) and the project-bound design of many restoration interventions (Tedesco et al 2023).…”
Section: Collecting Baseline Data and Restoring Historicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The last feature highlighted by participants was the importance of pursuing a long-term vision for restoration projects. Although this might seem obvious, the long-term viability of restoration interventions is often neglected in practice (Frietsch et al 2023). This is, among others, caused by limited funding (Höhl et al 2020) and the project-bound design of many restoration interventions (Tedesco et al 2023).…”
Section: Collecting Baseline Data and Restoring Historicalmentioning
confidence: 99%
“…On the social side, inflexible or short-sighted governance structures can slow restoration activities or promote misplaced restoration goals (Jepson 2022), and restoration projects face complex questions surrounding equity and inclusive participation (Elias et al 2021;Osborne et al 2021). Finally, a lack of adaptive capacity and resilience to complex social-ecological threats can jeopardize the longterm sustainability of restoration efforts (Dudney et al 2022;Frietsch et al 2023). These and other challenges related to restoration raise an important question: what do the people who plan, manage, and implement restoration interventions perceive as most important for successful restoration?…”
Section: Introductionmentioning
confidence: 99%
“…The application of different conservation targets provides insightful clues for adaptive conservation in the future [64]. According to the ecological importance of the study area in the world and China, this study adopted the target of 30% and the aggressive target of 50% (slightly higher than the ECR).…”
Section: The Importance Of Distinguishing Priority Areas Separately F...mentioning
confidence: 99%
“…The research showed that the elevation, slope and topographic position were important factors in the formation of an ecosystem distribution pattern. Ecosystem adaptation refers to the process by which ecosystems adjust their structure and function in response to natural environmental changes and biological components interact with environmental factors to continuously adapt to environmental changes [8]. Ecosystem stability is the basis of this adaptation, and the restoration or reconstruction of ecosystems should first maintain their stability [9].…”
Section: Introductionmentioning
confidence: 99%